PERBANDINGAN 6 METODE FORECASTING DALAM PERAMALAN JUMLAH MABA STMIK PPKIA PRADNYA PARAMITA MALANG - Syaifulloh, Ali (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
College of Informatics and Computer Management (STMIK) Pradnya Paramita Malang is a campus engaged in information technology that is ready to be used in advancing education. STIMATA continues to introduce its existence to the wider community, it is hoped that the more people who know the campus can increase the number of students. Forecasting has an important role in human daily life, such as temperature forecasts, inventory forecasts, earthquake predictions, weather forecasts and others. Obtain accurate methods from 6 forecasting methods, namely Exponential-Smoothing, Exponential-Smoothing With Trend, Moving-Average, Trend-Analysis, Additive-Decomposition and Multiplicative-Decomposition in forecasting the number of students in the coming year. This study aims to predict the number of new students at STIMATA, by looking at the smallest error of Mean Square Error and the accuracy in the forecasting results of the 6 forecasting methods. So that by knowing the number of new students in the 2014-2015 academic year and in the following year, can help the institution in making decisions from the forecasting. The right method of 6 forecasting methods to predict the number of new STIMATA students is the Multiplicative Decomposition method by looking at the smallest error value in forecasting.